(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2025)
This article provides a comprehensive analysis of the psychological and pedagogical factors that influence the development of students’ intellectual competencies in the context of rapidly expanding digital education. The modern digital environment enhances learners’ cognitive processes, supports autonomous learning, strengthens critical and analytical thinking, promotes creativity, and improves the ability to make effective decisions in problem-based situations. At the same time, excessive or improperly structured use of digital technologies may lead to cognitive overload, reduced attention span, and a decline in academic motivation. The study explores key psychological determinants—perception, memory, thinking, metacognitive skills, cognitive flexibility—and core pedagogical factors such as digital instructional models, teachers’ digital competence, motivational strategies, and interactive methods of teaching. The findings reveal that digital education has significant potential to foster students’ intellectual growth; however, it requires scientifically grounded pedagogical approaches to ensure high levels of learning effectiveness.